Studying the Ability of Thymol to Improve Fungicidal Effects of Tebuconazole and Difenoconazole Against Some Plant Pathogenic Fungi in Seed or Foliar Treatments - Shcherbakova, Larisa; Mikityuk, Oleg; Arslanova, Lenara; Stakheev, Alexander; Erokhin, Denis; Zavriev, Sergey; Dzhavakhiya, Vitaly (Frontiers in Microbiology, 2021)
Thymol, a secondary plant metabolite possessing antifungal and chemosensitizing activities, disrupts cell wall or membrane integrity and interferes with ergosterol biosynthesis. Thymol also functions as a redox-active compound inducing generation of reactive oxygen species and lipid peroxidation in fungal cells. Previously, we showed thymol significantly enhanced the in vitro growth inhibitory effect of difenoconazole against Bipolaris sorokiniana and Parastagonospora nodorum. More recently, we demonstrated a possibility to use thymol to overcome the resistance of a P. nodorum strain able to grow on difenoconazole-containing media. However, potential for thymol to serve as a chemosensitizing agent in seed or plant treatments, to provide an effective suppression of the above-mentioned plant pathogens by triazole fungicides applied in lowered dosages, had yet to be tested. In the work presented here, we showed combined treatments of naturally infected barley seeds with thymol and difenoconazole (Dividend® 030 FS) synergistically exacerbated the protective effect against common root rot agent, B. sorokiniana, and other fungi (Fusarium spp. and Alternaria spp.). Similarly, co-applied treatment of wheat seeds, artificially inoculated with Fusarium culmorum, resulted in equivalent reduction of disease incidence on barley seedlings as application of Dividend®, alone, at a ten-fold higher dosage. In foliar treatments of wheat seedlings, thymol combined with Folicur® 250 EC (a.i. tebuconazole) enhanced sensitivity of P. nodorum, a glume/leaf blotch pathogen, to the fungicide and provided a significant mitigation of disease severity on treated seedlings, compared to controls, without increasing Folicur® dosages. Folicur® co-applied with thymol was also significantly more effective against a strain of P. nodorum tolerant to Folicur® alone. No additional deoxynivalenol or zearalenone production was found when a toxigenic F. culmorum was cultured in a nutrient medium containing thymol at a concentration used for chemosensitization of root rot agents. Accordingly, F. culmorum exposure to thymol at the sensitizing concentration did not up-regulate key genes associated with the biosynthesis of trichothecene or polyketide mycotoxins in this pathogen. Further studies using field trials are necessary to determine if thymol-triazole co-applications result in sensitization of seed- and foliar-associated plant pathogenic fungi, and if thymol affects production of fusarial toxins under field conditions.